Settlers-Indigenes Question in Nigeria: Much Rhetoric, No Answers - Akintola, Olusola E.; Yabayanze, Akumka Joseph (European Scientific Journal, ESJ, 2017)
Nigeria operates a federal system of government whereby Nigerians can reside in any part of the country and enjoy the rights and privileges of being the citizens of the country. However, the experiences of the citizens across the states of the federation have proved that this ideal is not true in all instances. The authors, therefore, examined settlers-indigenes question in Nigeria placing the theoretical citizenship as contained in the 1999 Constitution (as amended) side-by-side with the reality of the country. Secondary source of data collection was adopted as our methodology. Through this method, explanatory and deductive analysis was made. The findings of the paper revealed that settlers-indigenes question is negatively affecting Nigerian federalism and the peaceful co-existence of citizens. It was, therefore, recommended that Section 147 of the 1999 Constitution (as amended) which encourages indigeneship should be expunged or amended as it reinforces division and heightens settlers-indigenes question in the country.